UiTM-FSQD Negeri Sembilan collaborate to launch the first Food Safety for Young Generation (FOOYOO) programme in Negeri Sembilan / Nursabrina Munawar and Eddie Ti Tjih Tan - Munawar, Nursabrina; Tan, Eddie Ti Tjih (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The Food Technology Department, Faculty of Applied Sciences, Universiti Teknologi MARA Cawangan Negeri Sembilan (UiTMCNS), in collaboration with the Food Safety and Quality Division (FSQD) of the Negeri Sembilan State's Health Department, jointly organised the inaugural “Food Safety for Young Generation" (FOOYOO) Programme in Negeri Sembilan on 6th December 2022. This one-day programme was fully sponsored by FSQD and took place at the UiTMCNS Kuala Pilah Campus. The programme successfully attracted 50 undergraduate students. The collaboration was initiated in 2020 but experienced delayed due to Covid-19 Movement Control Order. FOOYOO is aimed at the younger generation, with the goal of developing student's potential by making food safety a Unique Selling Point (USP) in their processional development and careers, aligning with the principles of Industrial Revolution 4.0.